Public Diplomacy as an Instrument for Obtaining Foreign Policy Goals of the USA in Central Asia - B. Bahriev (Международная аналитика)
The article deals with the features of public diplomacy resource’ application in US foreign policy in Central Asia. The author claims that American public diplomacy which has been actively working in the region since the collapse of the USSR appears to be an important instrument of achievement of not only regional, but also global objectives of the USA. Despite a certain de-emphasis on the Central Asian direction in the American foreign policy at the present stage, the rising Russian public diplomacy activity and increasing Chinese influence in the region forces Americans to look for public diplomacy response in order to secure their positions in this important, from geopolitical viewpoint and energy resource perspective, region. The aforementioned tendencies shape a competitive regional environment for implementation of public diplomacy.